Pengaruh Inflasi dan Nilai Tukar Terhadap Indeks Harga Saham Gabungan Tahun 2017-2022 - Fanani, Naufal Liza; Aji, Toni Seno (Jurnal Ekonomika : INDEPENDEN, 2023)
The composite stock price index is a collection of historical data relating to changes in the price of a compound stock over a certain period of time, which is useful as a measure of the performance of common stock in world markets. Quantitative method is a type of research in this study with an observation period of 2017-2022. In this study, the source used is non-primary data, namely data that supports the variables studied. The data in this study contained independent variables, namely: Inflation and, Rupiah exchange rate. Data from the dependent variable is the JCI. This study resulted in the rupiah exchange rate having an impact on the joint stock price index and inflation not having an impact on the Jakarta Composite Index, while the rupiah exchange rate and inflation simultaneously having an impact on the joint stock price index by 35.5% and then the rest of the other variables which are not. used in this study which can affect the Y variable by 64.5%. Keyword : Rupiah exchange rate, Inflation, Composite Stock Price Index.